Implementation of E-Book Media in Islamic Cultural History Learning at MTs Al Huda Tulung Balak - Hana Fauziah; Choirudin Choirudin; Siti Roudhotul Jannah (Assyfa Journal of Islamic Studies, 2026)
This study examines the implementation of e-book media in Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) learning at MTs Al Huda Tulung Balak. The research employs a qualitative approach with a phenomenological method to explore the planning, implementation, and evaluation of e-book usage in SKI instruction. Data were collected through in-depth interviews, observation, and documentation involving SKI teachers, eighth-grade students, and the madrasah principal. The findings reveal that: (1) e-book integration has been systematically incorporated into lesson planning through the Rencana Pelaksanaan Pembelajaran (RPP) and teaching modules, with materials structured progressively from general historical frameworks to specific events, figures, and Islamic cultural values; (2) the implementation phase demonstrates enhanced student engagement, active participation, and improved comprehension of narrative and conceptual SKI materials through the interactive features of e-books, fostering a student-centered learning environment where teachers act as facilitators; and (3) evaluation through written tests, assignments, and observation shows positive impacts on student motivation and learning outcomes, with increased analytical understanding and higher average scores compared to conventional instruction. However, challenges persist including limited access to personal digital devices among students, varying levels of digital literacy, and technical issues such as unstable internet connectivity. This research contributes theoretically to the development of digital media integration in Islamic education and practically provides concrete guidance for teachers, madrasah administrators, and policymakers in implementing e-book-based learning innovations relevant to 21st-century educational demands.